Prendrons-nous les usines ? : des comités d'entreprises à la gestion ouvrière. - Charpy, Suzanne; Bernard, Pierre (Paris : Lefeuvre, 1946)
Fonds Perrone
Frans
Monografie
Keywords: ondernemingsraden; zelfbeheer